PROFILE OS SPIROMETRY AND CLINICAL OUTCOMES OF SCHOOL-AGE CHILDREN IN THE UNIVERSITY HOSPITAL OF PARANÁ. (Fiep Bulletin - online, 2011)
The spirometry is a method for measuring lung function used solve diagnostic hypotheses and to monitor and quantificate lung disorders. Studies in the area of pediatric pulmonology and spirometry have great relevance, since in recent years, respiratory diseases has been a major cause of infant morbidity and mortality and major factor for hospitalization among children in the country. Whereas, the primary aims of this study were to analyze and quantify the spirometric parameters FVC and FEV1, FEV1/FVC and relate the type of disorder with clinical parameters (history of passive smoking, level of dyspnea, cough and wheezing). The study was realized at the University Hospital of Paraná, from the analysis of spirometric tests performed in the period June 2005 to July 2009, in children 5-12 years. There were 61 tests, where 46 were complete and were assessed for symptoms and spirometric data. It was used a significance level of 5% and analysis by Qui-Quadrado and t Student test. The data analysis showed that 37% of subjects had pulmonary function disorder. Of these, ten were obstructive mild, six moderate obstructive and severe obstructive with a reduction in forced vital capacity. The analysis of clinical data, passive smoking and symptoms of cough and wheezing had similar presentation between the groups (mild, moderate and severe), there was no relation no correlation between the parameters. It was concluded that the mild obstructive is the most frequent disorder children aged between five and 12 years. There is the possibility the exposition to the passive smoking and the symptoms such as coughing and wheezing were not significantly associated with the occurrence of pulmonary function disorders.
Keywords: spirometry; child; airway obstruction